Mentalisation-based online intervention for psychologically distressed parents: protocol of a non-randomised feasibility trial of the Lighthouse Parenting Programme-Online (LPP-Online) - Georg, Anna; Holl, Julia; Taubner, Svenja; Volkert, Jana (BMJ open, 2024)
Introduction Online-based interventions provide a low-threshold way to reach and support families. The mentalisation-based Lighthouse Parenting Programme is an established intervention aimed at preventing psychopathological development in children. The objective of this study is to examine the feasibility of an online adaptation of the Lighthouse Parenting Programme (LPP-Online), evaluating (a) recruitment capability, compliance, acceptability and satisfaction with the intervention; (b) the psychometric properties of and the acceptability regarding the adjunct psychological evaluation; and (c) the employed materials and resources. The study will also obtain a preliminary evaluation of participants’ responses to the intervention. - Method and analysis In this monocentric, one-arm, non-randomised feasibility trial, n=30 psychologically distressed parents with children aged 0 to 14 years will participate in the LPP-Online for a duration of 8 weeks. The intervention consists of online group sessions and individual sessions, 38 smartphone-based ecological momentary interventions (EMI), and psychoeducational materials (website, booklet). At baseline (T0) and the end of the intervention (T1), parents complete self-report questionnaires as well as 7-day ecological momentary assessments (EMA) via smartphone. During the intervention, additional EMA are completed before and after the daily EMI. An interview regarding parents’ subjective experience with the intervention will be conducted at T1. The feasibility of the intervention, the psychological evaluation and the resources will be examined using descriptive and qualitative analyses. The preliminary evaluation of the parents’ response to the intervention will be conducted by analysing pre-post changes in questionnaire measures and the 7-day EMA as well as data of additional EMA completed before and after the daily EMI. - Ethics and dissemination Ethical approval of the study has been obtained from the local ethics board (Faculty of Behavioural and Cultural Studies, University of Heidelberg). Consent to participate will be obtained before starting the assessments. Results will be disseminated as publications in peer-reviewed scientific journals and at international conferences. - Registration details German Clinical Trials Register (DRKS00027423), OSF (https://doi.org/10.17605/OSF.IO/942YW).
Gesehen am 05.12.2024